Demand for paid domestic labor in urban Peru - Garavito, Cecilia (2018)
The aim of this article is both to analyze the determinants of the probability of demanding paid domestic work (PDW), and to estimate the demand of the households for these services. Given that that the majority of the domestic workers are in the cities, we are going to analyze this demand in the urbane area. We will work with the Encuesta Nacional de Uso del Tiempo (ENNUT) and the Encuesta Nacional de Hogares (ENAHO), for the years 2010, and with the ENAHO 2016. Regarding the probability of hiring domestic paid work, we find that even if the demand for live—in domestic work is falling if compared with live—out domestic work, that type of arrangement subsists for «older» and richer households, while the younger household hire mostly live—out paid domestic workers. We also find that higher labor and non—labor earnings have a positive effect on the probability of hiring PDW in relation to not hiring it, and the marginal effects of the labor earnings of the spouse are higher for live—in workers, and the effect is the opposite for live – out workers. Regarding the demand of paid domestic work, we find that the hours demanded have a negative relation with the wage paid to the domestic worker and a positive relation with the family earnings. More so, there is a substitution effect between the domestic work done by the members of the household and the hours worked by the paid domestic workers. Additionally, the presence of women in the household reduces the hours of live—in paid housework demanded. Finally, the labor journey is longer if the employer lives in Lima Metropolitana, which is related to the fact that the capital city is the greatest market for paid housework in Peru, and also where the majority of these workers are.